Union list serials in libraries of the United States and Canada (New York : Wilson, 1965)
" Under the sponsorship of the Joint Committee on the Union List of Serials with the cooperation of the Library of Congress funded by a grant from the Council on Library resources, Inc." First edition published in 1927. this third edition incorporates the contents of the second edition (1943) and its two supplements together with new titles and additional locations. this edition represents the holdings of 956 cooperating libraries and includes 156, 449 titles. List of Coopcerating Libraries (with abbreviations) and Explanations in each volume.
Contents: v.1: A-B; v.2: C-G; v.3: H-M; v. 4: N-R; v.5: S-Z
Keywords: Periodicals -- Bibliography -- Union lists; Libraries -- U. S; Libraries -- Canada; Bibliography -- Bibliography -- Periodicals